PENYELESAIAN SENGKETA RUMAH TANGGA PERSPEKTIF TAFSIR BUYA HAMKA TERHADAP SURAT AN-NISA AYAT 34 – 35 - Oktorinda, Tri (UIN Fatmawati Sukarno Bengkulu, 2017)
This research raises the problem of Household Dispute Resolution Perspective Tafsir Buya Hamka Against Surat An Nisa Verse 34 - 35. The purpose of this study to describe the Settlement of Household Dispute Perspective Tafsir Buya Hamka Against Surat An Nisa Verse 34 - 35. The method used in research Library research. The results of this study that by overcoming the wickedness of the wife by giving advice and guidance, separating the bed or silent in bed, and a resuscitate punch. In the case of husband nusyuz, Islam offers peace, could with the initiative of the wife of both parties introspection each other. In order to maintain a home network, being mutually legowo to give the best for the couple is a recommendation. If indeed both parties are no longer able to be reconciled, you should take a way by using a good 3rd party is willing to solve the problem.